1992
DOI: 10.1071/wr9920405
|View full text |Cite
|
Sign up to set email alerts
|

Breeding biology and movements of Australian sea-lions, Neophoca cinerea, off the west coasst of Western Australia

Abstract: The Australian sea-lion, Neophoca cinerea, has a 17-18-month breeding cycle on islands off the west coast of Western Australia. Buller, North Fisherman and Beagle Is are the main pupping sites, with several very small colonies (n> 3) at the Abrolhos Is. The 4-5-month pupping seasons are synchronised at North Fisherman and Beagle Is, but the sea-lions from Buller I. breed one month later and those from the Abrolhos Is two months earlier. Pup production and pup mortality were highly variable between seasons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 4 publications
1
35
0
Order By: Relevance
“…Distances among the six South Australian colonies included in this study varied from only a few kilometers to almost 400 km. Clear differences in the genetic composition were observed between the most eastern and western South Australian colonies, which are close to the limit of expected dispersal capabilities (Gales et al, 1992;Lowther et al, 2013). However, significant structuring was also detected between colonies separated by only 120-160 km, well within realistic swimming distances for Australian sea lions.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 54%
See 2 more Smart Citations
“…Distances among the six South Australian colonies included in this study varied from only a few kilometers to almost 400 km. Clear differences in the genetic composition were observed between the most eastern and western South Australian colonies, which are close to the limit of expected dispersal capabilities (Gales et al, 1992;Lowther et al, 2013). However, significant structuring was also detected between colonies separated by only 120-160 km, well within realistic swimming distances for Australian sea lions.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 54%
“…Like most pinnipeds, Australian sea lions are capable of longrange movements and have been documented moving up to 350 km (Gales et al, 1992;Lowther et al, 2013). The aim of this study was to determine whether previously observed extreme matrilineal substructure is also evident with biparentally inherited microsatellite markers and whether typical mammalian male-biased dispersal is evident for this species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They are endemic to Australia, distributed from the Houtman Abrolhos Islands (WA) to The Pages Island (SA; [442]), in waters up to 105 m depth [443]. The species has been known to venture to the southern coast of eastern Australia.…”
Section: Neophoca Cinerea-australian Sea Lionmentioning
confidence: 99%
“…Breeding takes place aseasonally on average every 17.4 mo (range: 16.0− 19.9 mo) and asynchronously between breeding locations, during a period of 5 to 9 mo (Ling & Walker 1978, Gales et al 1992, Higgins 1993, Goldsworthy et al 2008. Haul-out sites in the Perth metropolitan area (Western Australia), approximately 250 km south of the closest breeding islands at Jurien Bay, are known to be used exclusively by males (Gales et al 1992). Male N. cinerea travel significant distances away from breeding colonies, presumably to maximise foraging success and efficiency (Gales et al 1992).…”
Section: Introductionmentioning
confidence: 99%